PENGARUH MENCUCI TANGAN TERHADAP ANGKA KUMAN PADA TELAPAK TANGAN SISWA SEKOLAH DASAR - Maulina, Rida; Harlita, Tiara Dini; Kusumawati, Nursalinda (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Washing hands with soap is one method of protecting the body from many infectious illnesses. Following the guidelines of the World Health Organization, effective hand washing involves six stages. The purpose of this study is to ascertain how proper and good hand washing habits affect the quantity of germs on the palms of pupils at State Elementary School 005 Samarinda. Purposive sampling was utilized to choose 31 samples for a quasi-experimental study with a one group pretest-posttest design. Through counseling, samples taken in the form of palm swabs and examined before and after hand washing were evaluated using the Total Plate Number (ALT) technique with dilutions ranging from 101 to 102. The Wilcoxon Test technique was used to assess the test findings using univariate and bivariate analysis. According to studies, there are typically 78 CFU/cm2 of germs on the hands before washing them, and there are 10 CFU/cm2 of germs after washing them with soap, with a 79% reduction in the quantity of germs on the palms. The Wilcoxon test findings showed a p-value of 0.000, indicating that there was a reduction in the number of germs on primary school children' palms both before and after washing their hands. Always wash your hands before and after carrying out activities.